2010
DOI: 10.1038/sj.bjc.6605505
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiling reveals novel epigenetically regulated genes and non-coding RNAs in human testicular cancer

Abstract: BACKGROUND: Testicular germ cell tumour (TGCT) is the most common malignant tumour in young males. Although aberrant DNA methylation is implicated in the pathophysiology of many cancers, only a limited number of genes are known to be epigenetically changed in TGCT. This report documents the genome-wide analysis of differential methylation in an in vitro model culture system. Interesting genes were validated in TGCT patient samples. METHODS: In this study, we used methylated DNA immunoprecipitation (MeDIP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 43 publications
4
87
1
1
Order By: Relevance
“…Epigenetic regulation by CpG methylation of these miRs could be cell line specific or other epigenetic mechanisms and specific transcriptional factors might interfere with the expression. Bisulfite conversion and methylation-specific PCR supported the existing data and also revealed that miR-34a, miR-199a1, miR-199a2 and miR-199b promoters were hyper-methylated and inversely correlated with their expression in a panel of cancer cells (Lodygin et al, 2008;Garzia et al, 2009;Cheung et al, 2010). Our data shows in particular that miR-199a1 and miR-199b promoters were hypermethylated in NSCLC, BRC and CRC cell lines.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Epigenetic regulation by CpG methylation of these miRs could be cell line specific or other epigenetic mechanisms and specific transcriptional factors might interfere with the expression. Bisulfite conversion and methylation-specific PCR supported the existing data and also revealed that miR-34a, miR-199a1, miR-199a2 and miR-199b promoters were hyper-methylated and inversely correlated with their expression in a panel of cancer cells (Lodygin et al, 2008;Garzia et al, 2009;Cheung et al, 2010). Our data shows in particular that miR-199a1 and miR-199b promoters were hypermethylated in NSCLC, BRC and CRC cell lines.…”
Section: Discussionsupporting
confidence: 86%
“…In general, it implies different stages of controlling mechanisms of a gene, especially of an oncogene. Moreover, miR-34a and miR-199a2 are reported that they are epigenetically controlled by CpG methylation (Lodygin et al, 2008;Cheung et al, 2010). 5-Aza treatment significantly induced the expression of either one or all of the miRs (miR-34a, miR-199a and b) in the screened cell lines.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MeDIP-CGI-arrays, however, are relatively reliable in identifying high DNA methylation differences within the same region between different samples, as was expected. 38 These arrays perform less reliably in distinguishing intermediate methylation differences between samples (r = 0.56 for IQR, Fig. 1B) and in classifying different CGIs in the same sample according to their methylation levels.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…In addition to the specific genes subject to DNA methylationmediated silencing reviewed by these authors, other studies on endocrine tumours have adopted genomewide approaches to identify potential novel epigenetically silenced genes. These types of studies on testicular (Cheung et al 2010) and ovarian cancer (Michaelson--Cohen et al 2011) have utilised MeDIP enrichment and on pancreatic tumours and ovarian cancer have used pharmacologic unmasking approaches (Kang et al 2010, Shimizu et al 2011. Still other studies on pituitary and thyroid tumours have described drug-induced unmasking techniques of histone tail modification that impact upon gene expression in these tumour types (reviewed in Farrell (2006), Ezzat (2008) and Yacqub-Usman et al (2012)).…”
Section: Endocrine Cells and Epigeneticsmentioning
confidence: 99%